Prediction of Mechanical Properties of Igneous Rocks Under Combined Compression and Shear Loading Through Statistical Analysis - He, Qingyuan; Li, Yingchun; Xu, Jinhai; Zhang, Chengguo (Rock mechanics and rock engineering, 2020)
Mechanical responses of rocks to combined compression and shear have attracted increasing attention but still lack comprehensive understanding. Sixty-eight laboratory tests are conducted on basalt and granite specimens sourced from different origins to generalize the effects of specimen inclination on the mechanical properties of igneous rocks. A novel regression model is established to predict peak strength and elastic moduli of igneous specimens at various inclination angles. The model mechanically considers both the individual effect and the combined effect of independent factors. It is found that specimen inclination has nearly the same effects on the failure patterns, strength, and elastic moduli of all the experimented igneous rocks regardless of origins. Igneous rocks tend to fail in shear under combined compression and shear loading. Both their strength and elastic moduli decline approximately linearly as specimen inclination increases. The reductions of both the strength and the elastic modulus as specimen inclination increases are closely associated with the UCS ( θ = 0°) and the Young’s modulus ( θ = 0°), respectively. The ratio of the peak strength to the elastic modulus is an inherent property of the igneous specimen, independent of the specimen strength and inclination.